Hubungan tingkat kecemasan terhadap aktivitas sehari-hari pada lansia di Panti Werdha Wana Seraya, Denpasar - Bali - Hendra Kusuma, Ida Bagus Gede; Ardani, IGA Indah (E-Jurnal Medika Udayana, 2018)
Elderly was the culmination of human life through the aging process. With increasing age, the risk of many chronic diseases can occur. This causes anxiety in the elderly over fears suffering from illness. One of the most common cause of anxiety in the elderly is social support, especially in the elderly in social institutions. Anxiety is a psychological disorder, with characteristic such as a recurring fear, causing loss of concentration in performing everyday activities. The aim of this study was to analyze the relationship between the level of anxiety about the daily activities of the elderly in social institutions Werdha wana while, Denpasar-Bali. The type of research was analytic research, which aims to find the relationship between variables with cross-sectional approach. Sampling in this study was the use of total sampling, which means all members of the population can be sampled, which numbered 40 people. The results provided the data that the elderly are not worried as much as 1 (9.1%) experienced dependency and as many as 10 people (90.0%) can perform activities independently. Elderly with anxiety were as many as three people (13.6%) experienced dependency and 19 others (86.4%) can perform activities independently. Elderly with severe anxiety as much as one person (14.3%) experienced dependency, while as many as 6 people (85.7%) can perform activities independently. The results of data processing using SPSS produced a value of p = 0.923 (p> 0.05), so that Ho is accepted and meaning of this study did not have a statistically significant relationship between the level of anxiety about the daily activities in the elderly in Elderly Social Institution Wana Seraya, Denpasar -Bali Keywords: Elderly, Anxiety, Daily Activities